PERSEPSI ORANG TUA TERHADAP PENDIDIKAN SEKSUAL PADA REMAJA - Parwati, Luh Dewi; Pramitaresthi, I Gusti Ayu; Antari, Gusti Ayu Ary (Coping: Community of Publishing in Nursing; Vol 9 No 4 (2021): Agustus 2021DO - 10.24843/coping.2021.v09.i04.p11, 2021)
Premarital sexual behavior is a person's behavior due to sexual stimulation which can be done alone, with the opposite sex, or same sex without being bound by a marriage. One of the efforts to prevent premarital sexual behavior in adolescents is sexual education. Parents' perceptions of sexual education are the perspective of parents related to providing understanding to adolescents about matters relating to sexuality. This study aims to find out and explore parents' perceptions of sexual education in adolescents in the Kuta District of Badung Regency. A qualitative research with a phenomenological approach was used in this study. Participants are mothers who have teenagers aged 14-17 years. The method applied to determine the participants was purposive sampling. The data were collected using in-depth interview procedures and field observations on 6 participants in Kuta District (March-May 2020). The data were analyzed using Colaizzi method. The results of this study consist of six themes, namely 1) Parents' perceptions of the vulnerability of premarital sexual behavior in adolescents;  2) Parents' perceptions of the severity of premarital sexual behavior in adolescents; 3) Parents' perceptions of the benefits of sexual education in adolescents; 4) Parents' perceptions of barriers to sexual education in adolescents; 5) Cues to act for parents in providing sexual education in adolescents, 6) Self-efficacy of parents in providing sexual education in adolescents. Health workers were expected to be able to provide health promotion to improve parental knowledge regarding sexual education.